2017
DOI: 10.15406/jig.2017.04.00056
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Cloning and Sequencing of Poly 3-Hydroxybutyrate Synthesis Genes from Local Strain of Bacillus cereus mm7 and Expression them in E. coli

Abstract: Poly 3-hydroxybutyrate (PHB) is the most known degradable biopolymers, produced by some genera of bacteria under unfavorable growth conditions. Isolation, cloning, and expression of PHB genes from PHB producing Bacillus cereus was achieved. A highest Poly 3-hydroxybutyrate producer bacterium was selected and identified as Bacillus cereus MM7, based on morphological and physiological characters in addition to 16S rRNA gene sequences. The four genes of Bacillus cereus MM7 that involved in Poly 3-hydroxybutyrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In another study, Tomizawa et al ( 2011 ) have engineered a recombinant construct harbouring phaR and phaC from Bacillus cereus complemented with phaA and phaB from R. eutropha to yield 7.44 g/L of PHB. Recently, El Rabey et al ( 2017 ) have reported the construction of a recombinant system exclusively using the PHB synthesis genetic background from B. cereus , but PHB accumulation was not mentioned. A few other studies on PHB production by recombinant E. coli incorporating genetic elements from Gram negative bacteria have reported a maximum yield of 0.21 g/L and 2.02 g/L (Arifin et al 2011 ; de Almeida et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Tomizawa et al ( 2011 ) have engineered a recombinant construct harbouring phaR and phaC from Bacillus cereus complemented with phaA and phaB from R. eutropha to yield 7.44 g/L of PHB. Recently, El Rabey et al ( 2017 ) have reported the construction of a recombinant system exclusively using the PHB synthesis genetic background from B. cereus , but PHB accumulation was not mentioned. A few other studies on PHB production by recombinant E. coli incorporating genetic elements from Gram negative bacteria have reported a maximum yield of 0.21 g/L and 2.02 g/L (Arifin et al 2011 ; de Almeida et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%